Limulitella tejraensis, a new species of limulid (Chelicerata, Xiphosura) from the Middle Triassic of southern Tunisia (Saharan Platform). (14th August 2017) - Błażejowski, Błażej; Niedźwiedzki, Grzegorz; Boukhalfa, Kamel; Soussi, Mohamed
Abstract: Numerous well-preserved remains of a new limulid species from the Anisian-lower Ladinian (Middle Triassic) of the Tejra section of southern Tunisia are described. Comparisons are made with limulids from the Triassic deposits of Europe and Australia. The new specimens are congeneric with the type species of Limulitella, but show some morphological differences. Here we describe Limulitella tejraensis new species, a small limulid with semicircular prosoma, small and triangular opisthosoma, well-defined axial ridge, and pleurae along both ridges of the opisthosoma. The Tunisian Limulitella fossils are associated with conchostracans, bivalves, gastropods, and microconchids. Sedimentological and paleontological data from the Tejra section suggest freshwater to brackish-water conditions during the formation of the fossil-bearing interval and the influence of marine transgression into a playa-like environment. Supposed adaptation to the stressful environment sheds new light on the origin and survival of the extant limulines. This is the first report of limulid body fossils from the Triassic of North Africa and the first documentation of Limulitella in the Middle Triassic of northern Gondwanaland.